R&D and innovation activities of firms in the Czech Republic - Vokoun, Marek (2014)
This thesis emphasizes the role of firms' innovation activities in different stages of a typical innovation process. The theoretical background is enriched by a review of innovation determinants, a CDM model and a case-study of multinationals. The review results suggest that, on average, the typical firm that engaged in innovation between 1986 and 2006 is a large firm competing in international markets. Smaller firms, however, invested more in R&D, and no linear relationship was found between firm size and output characteristics. Cooperation on R&D projects increased overall innovation intensity. There is strong evidence that public funding had an ambiguous effect on R&D spending and no effect on innovation output. This output measured by sales from innovated goods and services was, on average, a positive determinant of labour productivity; however, a detailed study suggests this effect was present only for product innovation. Then, four Czech CIS waves (2001, 2003, 2006, and 2008) were analysed in the CDM model that describes the link between R&D expenditure, innovation output, and productivity. The estimated low innovation input elasticity around 10% describes the Czech companies as poor innovators in the EU. This economy was a transition country until 2006, and we have observed a substantive FDI inflow since 1998. Multinationals have a higher sales share now and are an essential part of the economy. Multinationals engage less in innovation, but spend more on R&D and appropriate more from their innovation projects. The FDI inflow was a form of innovation wave. Innovation output is an important determinant for boosting productivity among SMEs. Public support had no effect on innovation output. Lastly, the case study showed that multinationals are more productive, pay higher wages and have no long run impact on market concentration.